Perbandingan Pemberian Cairan Koloid dengan Pemberian Terapi Obat Ephedrine dalam Mencegah Terjadinya Hipotensi Pasca Anestesi Spinal pada Pasien Sectio Caesarea di RSUD Ajibarang - Mulina, Napa; Yudha, Magenda Bisma; Andini, Amelia; Suandika, Made (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Hypotension is one of the most common complications following spinal anesthesia, particularly in patients undergoing cesarean section. If not properly managed, it can lead to serious consequences such as nausea, vomiting, loss of consciousness, cardiovascular collapse, and decreased uteroplacental blood flow, which may endanger both the mother and fetus. Therefore, preventive measures are essential to ensure patient safety during surgery. This study aimed to compare the effectiveness of colloid fluid administration and intravenous ephedrine therapy in preventing hypotension after spinal anesthesia in cesarean section patients. This was a quantitative comparative study using a two-group pretest-posttest design, involving 80 respondents at RSUD Ajibarang. The subjects were divided into two intervention groups: one receiving colloid fluids and the other receiving intravenous ephedrine. Blood pressure measurements were taken before and after the interventions, and data were analyzed using paired sample t-tests and independent t-tests to assess intra- and inter-group differences.The results showed that both interventions were able to increase blood pressure; however, intravenous ephedrine administration was more effective in maintaining hemodynamic stability. A statistically significant difference was found in post-intervention measurements between the two groups (p = 0.046), with the ephedrine group demonstrating a higher mean arterial pressure compared to the colloid fluid group. These findings suggest that intravenous ephedrine is superior to colloid fluid administration in preventing post-spinal anesthesia hypotension during cesarean section. Ephedrine can therefore be considered a preferred intervention for improving maternal safety and reducing the risk of complications during cesarean procedures.